Subcapsular hepatic hematoma post-endoscopic retrograde cholangiopancreatography: a case report and literature review - Amador, Olga E.; Garcia, Gabriel Gutierrez; Gutierrez, Miguel Angel Echeverry (International Journal of Research in Medical Sciences, 2024)
A 23-year-old female with a history of long-standing obesity, recently was diagnosed with cholelithiasis, along with a 15 day development of jaundice. An ERCP (endoscopic retrograde cholangiopancreatography) was performed, during which resulted an unsuccessful sphincterotomy, this was followed by placing a 7-centimeter, 10 French Amsterdam-type stent, subsequently she experienced sudden abdominal pain, and a CT scan revealed a subcapsular hepatic hematoma, which required surgical management. The objective was to describe a clinical case of subcapsular hepatic hematoma, clinical presentation, and therapeutic conduct. The treatment of subcapsular hepatic hematoma will depend on the patient’s hemodynamic stability. However, survival is uncertain due to its rarity, making it crucial to recognize its early signs and symptoms and act promptly.